Proprotein Convertase 5/6 Is Critical for Embryo Implantation in Women: Regulating Receptivity by Cleaving ebp50 Modulating Ezrin Binding, and Membrane-Cytoskeletal Interactions - Velasquez, L (2011)
Sin Editorial Disponible